The logistics of police power: Armored vehicles, colonial boomerangs, and strategies of circulation. (December 2020) - Denman, Derek S
Images of police armored vehicles in Ferguson and Baltimore have been influential in a public conversation about the militarization of the police. However, recent critical and abolitionist work on policing rejects the concept of "militarization" for obscuring the longstanding histories and institutional connections between military and police apparatuses. By following the transfers of armored vehicles to police, this article illuminates the logistical pathways that connect colonial warfare and domestic policing, adding an account of the material composition of police power to the historical work of critical and abolitionist thinkers. The article proceeds through a critical reading of records of the Defense Logistics Agency, tracking the transfer of surplus armored vehicles to the police. Designated as "high-visibility property" by the Defense Logistics Agency, these vehicles testify to the materiality of police power. The article then tracks the visibility and materiality of these vehicles as they are deployed in urban and suburban spaces and considers their unique capacity to suppress the democratic energies of crowds. Tracking the armored vehicle provides a way to ask how the rigid lines of fortified urban space are organized into mobile vectors and where ongoing processes of colonization enter these spatial processes.